Development of Biawak Island digital encyclopedia for conservation biology lecture - Natadiwijaya, Ismail Fikri; Sugianto, Sugianto; Yuliana, Eva; Subkhi, Nur; Rachman, Dwi Fauzi; Luzyawati, Lesy (Nashir Al-Kutub Indonesia, 2023)
Conservation Biology is an interdisciplinary science whose purpose is to encourage the development of theory and application in conservation areas. Biawak Island is one of the leading conservation areas in the Indramayu district, therefore conservation biology learning should be done directly on Biawak Island. In practice, studying conservation biology directly on Biawak Island is difficult because of the long distance and expensive access to this place. Based on these problems, a digital encyclopedia of conservation on Biawak Island is needed to solve the problem of needing media that can become a medium for studying conservation in this hard-to-reach area. The method in this research is quantitative, and the research design is development research using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), but does not include implementation and evaluation phases. The name given to the encyclopedia is PULBIN PEDIA, which was created using the PHP programming language. The content includes a profile of Biawak Island and conservation on Biawak Island, which contains multimedia narrative text, images, and videos. The digital encyclopedia has a control device that allows users to explore the encyclopedia's contents independently and can be updated at any time by the administrator. The validation expert results show that the PULBIN PEDIA encyclopedia is very valid as a learning medium for students and college students.